The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.15288/jsad.2009.70.169
|View full text |Cite
|
Sign up to set email alerts
|

Childhood ADHD and Conduct Disorder as Independent Predictors of Male Alcohol Dependence at Age 40

Abstract: ABSTRACT. Objective: The Danish Longitudinal Study on Alcoholism was designed to identify antecedent predictors of adult male alcoholism. The infl uence of premorbid behaviors consistent with childhood conduct disorder (CD) and attention-defi cit/hyperactivity disorder (ADHD) on the development of alcohol misuse was examined. Method: Subjects were selected from a Danish birth cohort (9,125), which included 223 sons of alcoholic fathers (high risk) and 106 matched sons of nonalcoholic fathers (low risk). These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 40 publications
(43 reference statements)
4
40
0
Order By: Relevance
“…The retrospective Childhood Deviance Scale refl ects the adult subjects' self-ratings of 12 behaviors enacted during development to age 18, and contains internalizing and externalizing behavioral traits associated with hyperactivity, restlessness, aggression, shyness, withdrawal, and depression. The Childhood Deviance Scale correlated signifi cantly with comparable items collected 10 or 20 years earlier, such as the Childhood Conduct Disorder Scale (r = .56, p < .0001) and the School Teacher Questionnaire Behavioral Summary Score (r = .37, p < .0001) (Knop et al, 2009). The Psychosocial Interview also collected extensive data about the quantity and frequency of the consumption of beer, wine, and distilled spirits in the recent past and included the 32-item Alcoholism Severity Scale used in other studies by our group (Penick et al, 1987;Powell et al, 1992) to evaluate the major symptoms of alcoholic drinking both in the past year and over the subject's lifetime.…”
Section: Adult Outcome Measuresmentioning
confidence: 83%
“…The retrospective Childhood Deviance Scale refl ects the adult subjects' self-ratings of 12 behaviors enacted during development to age 18, and contains internalizing and externalizing behavioral traits associated with hyperactivity, restlessness, aggression, shyness, withdrawal, and depression. The Childhood Deviance Scale correlated signifi cantly with comparable items collected 10 or 20 years earlier, such as the Childhood Conduct Disorder Scale (r = .56, p < .0001) and the School Teacher Questionnaire Behavioral Summary Score (r = .37, p < .0001) (Knop et al, 2009). The Psychosocial Interview also collected extensive data about the quantity and frequency of the consumption of beer, wine, and distilled spirits in the recent past and included the 32-item Alcoholism Severity Scale used in other studies by our group (Penick et al, 1987;Powell et al, 1992) to evaluate the major symptoms of alcoholic drinking both in the past year and over the subject's lifetime.…”
Section: Adult Outcome Measuresmentioning
confidence: 83%
“…Previous literature has found that CMB is a good predictor of later alcohol dependence with shared environmental causes (e.g., Knop et al, 2009). CMB may evoke recurrent inept harsh CPP, in a coercive process that drives CMB forward and may contribute to precocious drinking and other alcohol outcomes (Fergusson et al, 2008).…”
Section: Cpp-aud Associationmentioning
confidence: 99%
“…In particular, conduct disorder (CD) and adolescent attention-defi cit/ hyperactivity disorder (ADHD) are often correlated with later alcohol use disorders, especially alcohol dependence (AD) (Arias et al, 2008;Friedrichs et al, 2010;Knop et al, 2009;Langley et al, 2010;Weiss et al, 1985;Whalen et al, 2002;White et al, 2001). Each of these disorders is characterized to some extent by externalizing behavior, raising the possibility that a general liability to such behavior contributes to the association among phenotypes.…”
mentioning
confidence: 99%